PEMAKAIAN KOMPETITIF: MACAM BIDANG DAN PENYEBAB - Setyadi, Ary (Faculty of Humanities, Diponegoro University, 2014)
The final result of writing the article, entitled â€œCompetitive usage: a wide field and cause â€related to the findings: still/can the discovery of two forms that are competitive in usage/communication, so from the relevant form correlated with the lack of certainty which of the form should be used. As a result, the existing problems of interest to be studied. The finding of the two forms is related to the fields: phonology, morphology, semantic, and etymology; as for the cause lies in the speaker itself. The basic approach used in interest of contradictory data analysis on linguistic theory. The stages of contradictory research on:Â Â Â Â Â Â 1. Data collection, 2. classification and analysis of data and 3. Stage of writing/reporting. For the benefit: which form should be used, then it is proper if the Indonesian speakers utilize existence: EYD handbook, a large dictionary and grammar Indonesian standard. Because the existence of the three sources of reading is meant to function as a â€œguidelineâ€.